Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/cmi.12285
|View full text |Cite
|
Sign up to set email alerts
|

The inner membrane complex through development ofToxoplasma gondiiandPlasmodium

Abstract: SummaryPlasmodium spp. and Toxoplasma gondii are important human and veterinary pathogens. These parasites possess an unusual double membrane structure located directly below the plasma membrane named the inner membrane complex (IMC). First identified in early electron micrograph studies, huge advances in genetic manipulation of the Apicomplexa have allowed the visualization of a dynamic, highly structured cellular compartment with important roles in maintaining the structure and motility of these parasites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 99 publications
(196 reference statements)
1
90
0
5
Order By: Relevance
“…Gametocytes possess an inner membrane complex (IMC) underneath their plasmalemma, which consists of flat membranous sacs, the alveoli, and supporting structural elements and which is thought to be required for the stability of the crescent‐shaped parasite stages (Dearnley et al ., 2012; Kono et al ., 2012; Simon et al ., 2013; reviewed in Harding and Meissner, 2014; Boucher and Bosch, 2015). During gametogenesis, the IMC disintegrates, resulting in gametes solely confined by the plasmalemma.…”
Section: The Formation Of Gametesmentioning
confidence: 99%
“…Gametocytes possess an inner membrane complex (IMC) underneath their plasmalemma, which consists of flat membranous sacs, the alveoli, and supporting structural elements and which is thought to be required for the stability of the crescent‐shaped parasite stages (Dearnley et al ., 2012; Kono et al ., 2012; Simon et al ., 2013; reviewed in Harding and Meissner, 2014; Boucher and Bosch, 2015). During gametogenesis, the IMC disintegrates, resulting in gametes solely confined by the plasmalemma.…”
Section: The Formation Of Gametesmentioning
confidence: 99%
“…For dinoflagellates and ciliates, largely aquatic groups, the IMC appears to have a predominantly structural role in cell architecture. However, for apicomplexans, an additional function is its role in cell motility and cytokinesis (5).…”
mentioning
confidence: 99%
“…To date, over 25 IMC resident proteins have been identified (3,5). Phylogenetic analysis has demonstrated that in addition to a common core set of conserved proteins, the IMC includes many lineage-specific proteins, reflecting additional adaptations to specialized requirements of the compartment within the respective phylogenetic group (6).…”
mentioning
confidence: 99%
“…The shape and functional integrity of the cell is dependentupon an elaborate cytoskeletal network that subtends a trilaminar membranous pellicle consisting of the plasma membrane and a subjacent platform of one or more flattened vesicles, the alveolar membranes, a feature that unifies the Alveolata [8][9][10][11] (Fig 1d). The alveolar membranes, together with their cytoskeletal infrastructure, constitute the inner membrane complex (IMC) of the pellicle, a domain of the parasite that has received significant attention given its role in anchoring the gliding motor complex [12].…”
Section: Apicomplexan Architecturementioning
confidence: 99%